Cyclic Pricing by a Durable Goods Monopolist - Conlisk, John; Gerstner, Eitan; Sobel, Joel (Quarterly Journal of Economics, 1984)
In the model of this paper a monopoly seller of a durable good holds periodic sales as a means of price discrimination. A new cohort of consumers enters the market in each period, interested in purchasing the good either immediately or after a delay. Within each cohort, consumers vary in their tastes for the good. Under broad conditions, the seller will vary the price over time. In most periods, he will charge a price just low enough to sell immediately to consumers with a high willingness to pay. Periodically, however, he will drop the price far enough to sell to an accumulated group of consumers with a low willingness to pay.